MEASUREMENT ERROR INDUCED BY AIR GAP OF ELECTROMAGNETIC-WAVE ABSORBER IN THE COAXIAL LINE METHOD - KIM, KY; KIM, WS; JUNG, HJ; JANG, SD (JAPAN J APPLIED PHYSICS, 1992)
The effect of an air gap between a specimen and a jig on the material constant (permittivity, permeability) and attenuation characteristics of electromagnetic wave absorbers in the coaxial line method was investigated. The presence of an air gap rendered both the measured permittivity and permeability lower than true values, where this tendency was greater in the case of permittivity. An inner gap, as compared to an outer gap, was found to yield a larger difference between measured and true values. The effect of the air gap was measured for Ni0.3Zn0.7Fe2O4, in which the gap was eliminated by metallization with an Ag-paste. The measured characteristics were in good agreement with corrected values of calculations.